2015
DOI: 10.1016/j.ydbio.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Tak1, Smad4 and Trim33 redundantly mediate TGF-β3 signaling during palate development

Abstract: Transforming growth factor-beta3 (TGF-β3) plays a critical role in palatal epithelial cells by inducing palatal epithelial fusion, failure of which results in cleft palate, one of the most common birth defects in humans. Recent studies have shown that Smad-dependent and Smad-independent pathways work redundantly to transduce TGF-β3 signaling in palatal epithelial cells. However, detailed mechanisms by which this signaling is mediated still remain to be elucidated. Here we show that TGF-β activated kinase-1 (Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 53 publications
2
40
0
Order By: Relevance
“…2F, J, arrow head), suggesting that caACVR1;K14-Cre mice have SMCP without cleft soft palate. Previous studies have demonstrated that one of the causes of SMCP in mice is MEE persistence (Dudas et al, 2006; Lane et al, 2014; Xu et al, 2006). To elucidate whether SMCP found in caACVR1;K14-Cre mice is due to the MEE persistence, we focused on MEE seam formation at E14.5 and E15.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2F, J, arrow head), suggesting that caACVR1;K14-Cre mice have SMCP without cleft soft palate. Previous studies have demonstrated that one of the causes of SMCP in mice is MEE persistence (Dudas et al, 2006; Lane et al, 2014; Xu et al, 2006). To elucidate whether SMCP found in caACVR1;K14-Cre mice is due to the MEE persistence, we focused on MEE seam formation at E14.5 and E15.5.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of TGFβ signaling in the basal epithelium in mice results in medial edge epithelium (MEE) persistence and complete cleft of the soft palate (Dudas et al, 2006; Lane et al, 2015; Xu et al, 2006). Palatal mesenchyme-specific deletion of Bmpr1a impairs palatal shelf growth and bone development, and causes submucous cleft of the hard palate (Baek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Tgfβ signaling can activate Smad-independent pathways, including the Tgfβ-activated kinase-1 (Tak1) and p38 MAPK kinase cascade (Derynck and Zhang, 2003). Studies of mice with epithelium-specific inactivation of Smad4 , Tak1 , and Trim33, show that all three pathways act partly redundantly to mediate Tgfβ3 signaling in palatal MES breakdown (Xu et al, 2008; Lane et al, 2015). …”
Section: Palatal Fusion: Formation and Dissolution Of Inter-shelf mentioning
confidence: 99%
“…(Bush and Jiang 2012;Mishina and Snider 2014;Smith et al 2012) Among the myriad of factors that have are expressed during development of the palate, transforming growth factor beta (TGF-β), fibroblast growth factor (FGF), and bone morphogenetic protein (BMP) signaling pathways have been shown to be essential for palate development. (Bush and Jiang 2012;Hill et al 2015;Lane et al 2015;Matsumura et al 2011;Parada and Chai 2012;Smith et al 2012;Yumoto et al 2013) Previous studies on the developmental deficits observed in the absence of CCN2 found craniofacial differences between CCN2 knockout (KO) compared to wild-type (WT) littermates. Allometric (size-based) and non-allometric shape differences were observed in CCN2 KO skulls, which were shorter and wider than their WT counterparts.…”
Section: Introductionmentioning
confidence: 99%